Unleashing the IoT Revolution in India: Trends, Advantages, Applications, and Strategic Importance - Tippannavar, Sanjay S; D, Yashwanth S (Journal of ISMAC, 2023)
The Internet of Things (IoT) represents a revolutionary paradigm where everyday objects are interconnected, enabling them to collect, exchange, and act upon data. This interconnectedness extends beyond traditional computing devices, incorporating a diverse range of physical objects embedded with sensors and actuators. The applications of IoT are vast and impactful, permeating various sectors globally. From smart homes and cities to industrial automation, healthcare, and agriculture, the IoT is driving unprecedented efficiency, convenience, and innovation. Worldwide, the growth of IoT is staggering, with billions of devices already connected and projections indicating exponential expansion. According to recent statistics, the global IoT market reached 201 billion in 2022, showcasing a 21.5% increase, and it is anticipated to surge further, underlining the pervasive integration of IoT into the daily lives of individuals and industrial activities. In the Indian context, the strategic importance of the IoT is paramount. With a rapidly expanding economy and a burgeoning population, India stands to gain significantly from IoT applications. The technology’s potential to address challenges in agriculture, healthcare, smart cities, and industrial processes aligns with national development goals. The implementation of IoT in India fosters efficiency, sustainability, and economic growth. As the IoT continues to evolve globally, its transformative impact on India’s socio-economic landscape solidifies its role as a catalyst for innovation and progress, promising a future where connectivity and intelligence converge for the betterment of individuals and the nation as a whole. With a focus on trends, contributions, advancements, and applications, this article seeks to broaden the knowledge around IoT in India and functions as a kind of reference for scholars interested in the subject.